2012
DOI: 10.4102/ojvr.v79i1.413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of packing on changes in erythrocyte osmotic fragility and malondialdehyde concentration in donkeys administered with ascorbic acid

Abstract: Experiments were performed with the aim of investigating the effect of packing on erythrocyte osmotic fragility (EOF) and malondialdehyde (MDA) concentration in donkeys, and the effect of ascorbic acid (AA). Twelve apparently healthy donkeys raised under the traditional extensive system served as experimental subjects. Six donkeys administered orally with AA (200 mg/kg) and subjected to packing were used as experimental animals, whilst six others not administered with AA served as controls. Blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…For instance, the initiation of pulmonary respiration causes changes in blood pH that could explain the higher osmotic fragility of the foal's erythrocytes. This is in accordance with previous studies carried out on donkeys, domestic fowl, cattle, pigs, rats, and rabbits that found a significant influence of blood pH on EOF. Some authors have concluded that the decrease in pH accelerates EOF by affecting the potassium–chloride co‐transporter on the red cell membrane in vitro.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For instance, the initiation of pulmonary respiration causes changes in blood pH that could explain the higher osmotic fragility of the foal's erythrocytes. This is in accordance with previous studies carried out on donkeys, domestic fowl, cattle, pigs, rats, and rabbits that found a significant influence of blood pH on EOF. Some authors have concluded that the decrease in pH accelerates EOF by affecting the potassium–chloride co‐transporter on the red cell membrane in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…Foals had a significantly higher EOF than mares at NaCl concentrantions of 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% from day 1 until day 18. The EOF in hypotonic solution has been studied in artiodactyls, humans, donkeys, camels, pigs, and horses affected by immune‐mediated hemolytic anemia . It has been shown that EOF is related to the morphologic characteristics and, particularly, to the size of the erythrocytes and their cell membrane integrity .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is thought to aggravate the symptoms of many diseases, including haemolytic anaemias, because erythrocytes are highly susceptible to oxidative damage induced by free radicals or reactive oxygen species [ 40 , 41 ]. Studies in goats, pigs and donkeys showed that stressful conditions such as transportation and packing induced a significant increase in the erythrocyte OF that was not present when the animals were treated with an anti-oxidant (ascorbic acid) before undergoing the stressful event, suggesting that the increased OF was a consequence of oxidative stress [ 41 - 43 ]. Although, not yet studied, oxidative stress may have similar effects on canine erythrocytes and may contribute to the increased OF that is seen in dogs with IMHA.…”
Section: Discussionmentioning
confidence: 99%
“…The erythrocytes therefore, become more fluid and allow more movement and permeability of the cells, thereby damaging them. Furthermore, high temperatures recorded during transportation may cause proteins of the erythrocytes membrane to denature, which may lead to membrane disintegration and haemolysis [7,10,25]. Thirdly, transport-induced oxidative stress on erythrocytes due to the adverse effect of toxic ROS, presumably generated during the transportation, may also contribute to the deterioration of erythrocyte properties; leading to increase in haemolysis.This is true because the erythrocytes are susceptible to oxidative stress as a result of high contents of unsaturated fatty acids in their membranes [1].…”
Section: Citationmentioning
confidence: 99%
“…The EOF may be employed as a biomarker and additional diagnostic tool for the assessment of transport-induce oxidative stress in quails. [7,10].The use of EOF as a biomarker of road transport-induced stress in livestock is a new field of study that may add to the arsenals of tests, currently used in the diagnosis of stress due to road transportation [11][12][13]. Body temperature measurement is an important method of evaluation of physiological status.…”
Section: Introductionmentioning
confidence: 99%